PENGARUH TEKANAN WAKTU, RISIKO AUDIT, MATERIALITAS, LOCUS OF CONTROL DANTINDAKAN SUPERVISI TERHADAP PENGHENTIAN PREMATUR ATASPROSEDUR AUDIT - Ardianto Samudro; Murtanto Murtanto (Jurnal Akuntansi Trisakti, 2017)
The purpose of this researchare to analyze time pressure, audit risk,materiality, Locus of control and supervision that can affect the premature sign off audit procedures. The population in this research is the auditors who work in the public accountant office in DKI Jakarta and as much as 113 respondents are selected as samples in this research. The collection of primary data is carried out by performing survey method which gives written questions in the form of questionnaires and directly distribute it to the respondents in each the public accountant office. The test of data is done the validity and reliability, as well as the normality test. The hypothesis was analyzed using the Multiple Regression Analysis as well as R2-test and T-test assisted with SPSS 20.0 the analyze for the effect of time pressure, audit risk, materiality, locus of control and supervision of the premature sign off audit procedures. The result of the study showed that the time pressure, materiality, Locus of control and supervision have effect positivelyand significant to the premature sign off audit procedures.